Mortality from Alzheimer's disease in Brazil, 2000-2009 - Jane Blanco Teixeira; Paulo Roberto Borges de Souza Junior; Joelma Higa; Mariza Miranda Theme Filha (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Alzheimer's disease is the most prevalent type of dementia in the elderly worldwide. To evaluate the mortality trend from Alzheimer's disease in Brazil, a descriptive study was conducted with the Mortality Information System of the Brazilian Ministry of Health (2000-2009). Age and sex-standardized mortality rates were calculated in Brazil's state capitals, showing the percentage variation by exponential regression adjustment. The state capitals as a whole showed an annual growth in mortality rates in the 60 to 79 year age bracket of 8.4% in women and 7.7% in men. In the 80 and older age group, the increase was 15.5% in women and 14% in men. Meanwhile, the all-cause mortality rate declined in both elderly men and women. The increase in mortality from Alzheimer's disease occurred in the context of chronic diseases as a proxy for increasing prevalence of the disease in the population. The authors suggest healthcare strategies for individuals with chronic non-communicable diseases